1993
DOI: 10.1177/105381519301700206
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Play Activities to Preschool Children with Disabilities

Abstract: The purpose of this study was to determine whether three preschool children with autism or autistic-like behaviors would learn and generalize pretend play activities targeted at two different play levels-a developmentally appropriate (DA) level and an age appropriate (AA) level-differently. The children's readiness for the DA play level was assessed with the Developmental Play Assessment (DPA) instrument (Lifter, Edwards, Avery, Anderson, & Sulzer-Azaroff, 1968). We taught individual exemplars from the two dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
119
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(128 citation statements)
references
References 47 publications
(47 reference statements)
3
119
0
6
Order By: Relevance
“…Good teaching practices and procedures share many common elements between developmentalists and behaviorists. Lifter, Sulzer-Azaroff, Anderson, Coyle, and Cowdery (1993) demonstrated that children made maximum progress in symbolic play learning when behavioral teaching practices followed a developmental sequence for deciding the content of the teaching. It would be helpful for researchers of specific models to discuss separately the content of teaching (the curriculum) and the process of teaching (the teaching procedures and practices used).…”
Section: Future Directions: Questions That Need Answersmentioning
confidence: 99%
“…Good teaching practices and procedures share many common elements between developmentalists and behaviorists. Lifter, Sulzer-Azaroff, Anderson, Coyle, and Cowdery (1993) demonstrated that children made maximum progress in symbolic play learning when behavioral teaching practices followed a developmental sequence for deciding the content of the teaching. It would be helpful for researchers of specific models to discuss separately the content of teaching (the curriculum) and the process of teaching (the teaching procedures and practices used).…”
Section: Future Directions: Questions That Need Answersmentioning
confidence: 99%
“…These findings should be considered in conjunction with the growing body of research in support of visual strategies (e.g. Ganz and Flores 2008;Johnson et al 2003) and the intermingling of behavioral and naturalistic approaches to intervention (Bernard-Optiz et al 2004;Lifter et al 1993;Malone 2003;Prizant and Wetherby 1998). Although it is critical to provide specific and direct instruction, even scripted dialogue to children with ASD, it is just as important to provide intervention in the natural environment during meaningful communicative interactions (Goldstein 2002).…”
Section: Discussionmentioning
confidence: 93%
“…Most recently, Hobson et al (2009) posited that the underpinnings of play are more complex than previously thought, proposing that the development of symbolic play involves the interrelation of multiple factors, including generativity, flexibility, social-emotional motivation, and perspective-taking. Moreover, play is intrinsically motivating to children, and the simple desire to play because it is fun should not be discounted (Hobson et al 2009;Lifter et al 1993).…”
Section: Introductionmentioning
confidence: 98%
“…In symbolic play, the theme of pretence evolves from playing with toys functionally as in constructing a building to playing with toys symbolically as pretending that a banana is a telephone [20]. In comparison with typically developing children at the same mental age, autistic children have significant delay in development of symbolic play [21].…”
Section: Clinical Picture and Rationalementioning
confidence: 99%